KONTRIBUSI DUKUNGAN SOSIAL ORANG TUA TERHADAP PROKRASTINASI AKADEMIK MAHASISWA YANG MELAKUKAN PJJ (PEMBELAJARAN JARAK JAUH) DI MASA PANDEMI - Sisterindah, Margaretta; Qomariyah, Nurul (Jurnal Ilmiah Global Education, 2023)
Academic Procrastination is the behavior of postponing school or university tasks, which leads to a pile-up of assignments. Social support is needed to reduce academic procrastination, especially in this Covid-19 situation. The aim of this research is to empirically examine the contribution of parental social support to academic procrastination among students engaged in Distance Learning during the pandemic. Data collection was done using a questionnaire method to measure parental social support (from both fathers and mothers) and academic procrastination. The scales used in this study were the parental social support scale and the academic procrastination scale. The sampling technique employed in this research was non-probability purposive sampling. The results indicate that there is a highly significant contribution of parental social support to academic procrastination among students engaged in Distance Learning during the pandemic, accounting for 11.6% of the variance. The remaining 88.4% is influenced by other factors not covered in the study. The Beta value indicating the influence of the variable of parental social support (father) on academic procrastination is -0.306 (p = 0.007), while the Beta value for parental social support (mother) on academic procrastination is -0.045 (p = 0.690). These results show that the influence of the parental social support (father) variable on academic procrastination is greater than the influence of the parental social support (mother) variable.